MEMPROGRAMKAN PENGENALAN MANAJEMEN ZAKAT INFAQ SHODAQOH DI DESA PURASEDA, KECAMATAN LEUWILIANG, KABUPATEN BOGOR - Tubagus Rifqy Thantawi; Bayu Purnama Putra; Derika Rudianto (Jurnal Pengabdian Kepada Masyarakat Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
This community service aims to program the introduction of Zakat Infaq Shodaqoh Management. The subjects of this community service are the people of Puraseda Village, Leuwiliang District, Bogor Regency, West Java Province. The result of this community service is to find out the accountability and management of Zakat Infaq Shodaqoh in Puraseda Village. It can be concluded that the management of Zakat Infaq Shodaqoh in Puraseda Village has been carried out transparently and accountably.